Bad Kitty Gets a Phone - Bruel, Nick (New York : Roaring Brook Press, 2021)
"Kitty has almost everything a cat could want, everything... except for a phone! To get a device of such magic and beauty, Kitty must do extra chores around the house for three whole months without complaining. Desperate times call for desperate measures, after all! Is Kitty up for such a Herculean task?"--Publisher description.
Keywords: Cats -- Fiction; Cell phones -- Fiction; Smartphones -- Fiction; Internet -- Fiction. -- Safety measures; Cats -- Comic books, strips, etc; Cell phones -- Comic books, strips, etc; Smartphones -- Comic books, strips, etc; Internet -- Fiction. -- Safety measures; Animal fiction; Humorous fiction; Graphic novels; Children's graphic novels